Evaluation of soybean cultivars for biological nitrogen fixation - Regina Jacques Bohrer, Temis; Hungria, Mariangela (Pesquisa Agropecuaria Brasileira, 1998)
This work aimed at selecting cultivars for higher nodulation and biological N2 fixation (BNF) as well as for nodulation restriction with Bradyrhizobium strains established in Brazilian soils. The evaluation was done with 152 soybean genotypes. The cultivars were inoculated under environmentally controled and axenic conditions and in the absence of mineral N, with each one of the following Bradyrhizobium elkanii strains: SEMIA 5019 (=29w), SEMIA 587 and SEMIA 566. None of the cultivars tested restricted completely the nodulation, although up to four fold differences in nodule number and mass were found. General mean of total N accumulated in shoots of all cultivars with all strains was of 50.24 mg N/plant. The cultivars that showed better symbiotic performance with all strains and accumulated 30% more N than the general mean were: Bossier, BR-29, J-200, and Ivaí. The five cultivars characterized by lower BNF rates were: BR-7, EMBRAPA 9, EMGOPA-313, FT-Canarana and Paranagoiana.
Keywords: Bradyrhizobium; Glycine max; inoculation; nodulation; symbiosis